Immediate Effect of Instrument Assisted Soft Tissue Mobilization (Iastm) On Upper Limb Spasticity in Stroke Patients: A Pilot Study - Joshi, Rushikesh; Prajapati, Keyur; Soni, Pooja; Patel, Tanvi; Bharadva, Payal; Joshi, Madhuri (Journal of Neonatal Surgery, 2025)
Background: Stroke is a quickly growing clinical manifestation of localised brain function disruption that lasts for 24 hours or longer and has no obvious explanation other than vascular origin. The onset of Spasticity is highly variable in the post-stroke period. Instrument Assisted Soft Tissue Mobilization (IASTM) is a revolutionary fascia and connective tissue therapy that enables therapists to effectively treat functional connective tissue tissue diseases. Aim of the Research: To evaluate the immediate effect of IASTM with conventional therapy on upper limb spasticity in stroke patients. Methodology: Twenty subjects were recruited according to inclusion and exclusion criteria. These subjects were randomly allocated into two groups (group A treated with conventional therapy and IASTM technique, group B treated with conventional therapy). Pre- and post-assessment of upper limb spasticity using the Modified Tardieu Scale (MTS) was done, followed by statistical analysis. Result: pre and post scores of MTS by using paired t test which indicates there was significant improvement in GROUP-A (P<0.05) and Comparison of post scores of both groups was done by using unpaired T- test which shows significant reduction in spasticity (P = 0.00*). Conclusion: IASTM shows significant reduction on upper limb spasticity in stroke patients